Refined active learning to reliably grasp Control Systems and Mechatronics at undergraduate level via a robotic hand - Zavala-Yoé, Ricardo; Urriza-Arellano, Bernardo A.; López-Caudana, Edgar O.; Ramírez-Mendoza, Ricardo A. (Frontiers in Education, 2025)
Even with many innovative learning methods, a clear, efficient, precise, and well-defined process to teach Mechatronics is still lacking. Although definitely Active Learning (AL) shows up offering a lot of possibilities in this sense, we consider that an improvement is still necessary. We propose here a careful monitoring scheme assisted by specialized software and hardware to achieve this goal. We called such a method Scientific-Technical Software Assisted Active Learning (SciTSA-AL). In this sense, the curriculum for this subject now incorporates the modeling, control, and construction of a mechanical hand. For this, the course content was divided into 10 weekly topics with two exams and a project each, keeping the final session to show the controlled robotic hand. As we paid a lot of attention to proposing intermediate projects that could adequately converge to the construction of the hand, we investigated the difference between the grades of the P projects and the X exams; Δ = X − P. Thus, our purpose was to conduct a statistical study to verify if the medians of Δ were significantly different from 0. This result was true at 5% of level in seven out of nine groups, indicating improvement via P. Afterwards, key groups 2009, 2021, and 2022 were contended similarly. Significant differences to zero were found in groups 2009 vs. 2021 and 2009 vs. 2022 (progress), but not in 2021 vs. 2022. Thus, our novel SciTSA-AL design via P succeeded at 95% of confidence in most cases. The complete development is described in this document.